2008
DOI: 10.1155/2008/638467
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bcl‐2 Expression and Caspase‐3 in STZ‐Induced Diabetic Rats

Abstract: We assessed the expression of Bcl-2 family members at both mRNA and protein levels as well as the Caspase-3 activity, in order to investigate the occurrence of apoptosis in hippocampus of STZ-induced diabetic rats. We selected twenty-four Wistar rats; half of them were made diabetic by intraperitoneal injection of a single 60 mg/kg dose of streptozotocin (STZ, IP), while the others received normal saline and served as controls. The expressions of Bcl-2, Bcl-xL, and Bax mRNA and proteins were measured using RT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
49
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 39 publications
8
49
0
Order By: Relevance
“…Other studies on PC12 cells indicated that apoptosis was induced when excess concentration of glucose led to an increase in Bax expression [52]. Investigations by Anarkooli et al revealed the activation of proapoptotic proteins and suppression of antiapoptotic proteins in hippocampus of STZ-induced diabetic rats at both mRNA and protein levels using Bax/ Bcl-xl ratios [43]. An analysis of the genes that were significantly regulated by LBC indicates that while several antiapoptotic genes were significantly up-regulated, some apoptotic genes were also significantly down-regulated.…”
Section: Anti-apoptosis Genesmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies on PC12 cells indicated that apoptosis was induced when excess concentration of glucose led to an increase in Bax expression [52]. Investigations by Anarkooli et al revealed the activation of proapoptotic proteins and suppression of antiapoptotic proteins in hippocampus of STZ-induced diabetic rats at both mRNA and protein levels using Bax/ Bcl-xl ratios [43]. An analysis of the genes that were significantly regulated by LBC indicates that while several antiapoptotic genes were significantly up-regulated, some apoptotic genes were also significantly down-regulated.…”
Section: Anti-apoptosis Genesmentioning
confidence: 99%
“…CARD8 is involved in pathways leading to the activation of caspases or nuclear factor kappa-B. Caspase enzymes play an effective role in apoptosis of neurons of central nervous system [43]. CASP1 belongs to the cysteine proteases family (caspases).…”
Section: Anti-apoptosis Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Jafari Anarkooli et al (9) demonstrated that Bcl-2 family gene expression and caspase-3 activity were altered in the streptozotocin (STZ)-induced diabetic rat hippocampus. Furthermore, Revsin et al (10) found that a glucocorticoid receptor antagonist normalized hippocampal alterations and cognitive impairment in STZ-induced diabetic mice.…”
Section: Introductionmentioning
confidence: 99%
“…89,80 Therefore, it is plausible to admit that neurodegenerative diseases and diabetic encephalopathy have a genetic and biochemical common ground. 4 Alzheimer's disease -type 3 diabetes AD is a neurological disorder characterized by profound memory loss and progressive cognitive and behavioral decline due to selective loss or dysfunction of neurons in specific brain regions/neural circuits, including the neocortex, hippocampus, and basal forebrain.…”
mentioning
confidence: 99%